Degenerative consumerism and the Greek crisis - Lallas, Dimitris; Zarikos, Iason; Sotiropoulou , Maria (Mania) (The Greek Review of Social Research, 2024)
In this paper, we highlight the way consumerism is conceptualized and the problematization of its relation to the Greek crisis, by analyzing the relevant articles in the Sunday edition of Kathimerini during the period 2010-2016. Utilizing the methodology of Thematic Analysis, we present the basic themes through which specific politics of signification of the consumerism and the multidimensional (not only fiscal) Greek crisis as closely intertwined phenomena emerge. The emergence of consumerism as a degenerative and pathogenic ethos in a central theme indicates politics of signification and problematization of consumerism as a cause, symptom and aggravating factor of the multidimensional crisis of the Greek social formation. These are mass address politics of meaning which seem to be part of the broader liberal perspective and attempt to interpret the Greek crisis through the analytical prism of consumption and, above all, consumerism.